ASUHAN KEPERAWATAN PADA PASIEN DENGAN HIPERTENSI DI KAMPUNG SASAK KELURAHAN LIMO KOTA DEPOK - Nasyahwa Rifa R.A (2023)
Background : Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic of more than 90 mmHg. The most common symptom in hypertensive patients is headache radiating to the neck. According to Maslow, pain is a physiological need that must be addressed immediately because if left unchecked it can cause other health problems such as insomnia, reduced physical mobility and self-care problems. The prevalence of hypertension according to WHO data for 2015 shows that around 1.13 billion people suffer from hypertension worldwide. In Indonesia, the death rate due to hypertension is 427,218 cases. Methods: this research was conducted using the case study method of nursing care in patients with hypertension from February 23 to March 1, 2023. Data collection was carried out through interviews, observation and documentation. Result: The nursing diagnosis in this case is that my pain is related to a physiological injury agent (hypertension). Nursing interventions carried out are identification of location, characteristics, duration, frequency, pain intensity, identification of pain scale, identification of factors that aggravate and relieve pain, provide non- pharmacological therapy to reduce pain, control the environment that aggravates pain, teach non-pharmacological techniques to reduce pain (deep breathing relaxation technique). Nursing implementation is carried out in accordance with established nursing interventions and carrying out nursing evaluations. Within 3x24 hours the problem of acute pain can be resolved. Conclusion: nursing care given to hypertensive patients can be resolved as evidenced by the reduced pain scale witha scale of 2 and the patient is able to independently implement actions to reduce pain that have been taught by nurses.